1999
DOI: 10.1121/1.427320
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetrical properties of a vibrating wire and their effects

Abstract: Some effects of the asymmetries causing a splitting of the fundamental natural vibrating frequency of a wire have previously been reported [Hanson et al., J. Acoust Soc. Am. 103, 2873 (1998)]. It has been demonstrated in this work on brass harpsichord wire that the splitting of the frequency is due to intrinsic properties of the wire itself and not of asymmetries in the end clamps. The two frequencies are associated with two definite orientations with respect to the wire. These two vibrational directions have … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2011
2011
2012
2012

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
1
2
0
Order By: Relevance
“…Previous studies suggested that voice gender categorization does not depend on pitch perception since there is a large overlap between male and female fundamental phonation frequencies. Here, along with other authors (Coleman, 1976; Klatt and Klatt, 1990; Mullennix et al, 1995; Whiteside, 1998; Hanson and Chuang, 1999; Lavner et al, 2000) we demonstrated that, indeed, voice gender categorization can be performed using timbre information only. Pitch equalized stimuli had an overall percentage of responses lower than the original voices (−14.6%), but the response curves and perceptual distances were similar (−0.009) to those observed with original voices, suggesting that voice gender perception (rather than performance) can operate on timbre information alone.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Previous studies suggested that voice gender categorization does not depend on pitch perception since there is a large overlap between male and female fundamental phonation frequencies. Here, along with other authors (Coleman, 1976; Klatt and Klatt, 1990; Mullennix et al, 1995; Whiteside, 1998; Hanson and Chuang, 1999; Lavner et al, 2000) we demonstrated that, indeed, voice gender categorization can be performed using timbre information only. Pitch equalized stimuli had an overall percentage of responses lower than the original voices (−14.6%), but the response curves and perceptual distances were similar (−0.009) to those observed with original voices, suggesting that voice gender perception (rather than performance) can operate on timbre information alone.…”
Section: Discussionsupporting
confidence: 85%
“…Thus, timbre is what allows differentiating two sounds that can have the same perceived pitch and loudness. The ability to perceive gender can therefore be mediated by vocal acoustical properties such as the fundamental frequency of phonation ( F 0) but also formant values ( F 1, F 2, F 3), glottal function, and spectral slope (Coleman, 1976; Klatt and Klatt, 1990; Mullennix et al, 1995; Whiteside, 1998; Hanson and Chuang, 1999; Lavner et al, 2000). …”
Section: Introductionmentioning
confidence: 99%
“…The differences found in the vowel structure might be related to a higher degree of glottal leakage in the actors’ voices that resulted in a more breathy speech. Hanson and Chuang (1999) summarized that breathy voices were characterized by more intense fundamental frequencies, broader bandwidths of the first formants and aspiration noise in the region around the third formant. Differences in the aspiration noise could not be detected in our stimulus set (unpublished data), but as the measurements of HNR in the higher frequency regions might be less reliable due to the weak signal intensity of the frequency band, the presence of aspiration noise cannot be ruled out completely.…”
Section: Discussionmentioning
confidence: 99%